Poetyka trzecia - Madejski, Jerzy (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The author of this article presents the new publication issued by Ryszard Nycz, "Poetyka doświadczenia" ("Poetics of Experience", Warsaw 2012) in the context of this researcher’s previous works. "Sylwy współczesne" ("Contemporary Silva Rerum", Wrocław 1984) is considered to be the first poetics. It is an attempt to depict the phenomena in the Polish literature of the 1960s and 1970s, which were largely affected by the aesthetics of the early Modernism. The second poetics is the volume "Literatura jako trop rzeczywistości" ("Literature as a Trope of Reality", Kraków 2002), which is a description of the modern literature (from the middle 19th century to the end of the 20th century). "Poetics of Experience" constitutes the third poetics, and - at the same time - it is the poetics of both the modern literature and the modern written works. It is also humanistic poetics since it is culture-oriented and since it singles out a humanistic text from all other written works.
The Third Poetics
Keywords: poetyka; poetyka doświadczenia; Nycz Ryszard